Ella: sus muchas caras. Traducir poesía autóctona desde teorías feministas y poscoloniales - Chávez, Lidoly (2015)
The translation of Louis Halfe’s work into Spanish is only the first step in reflecting on the limited circulation of female indigenous literatures in the Americas. Through the linguistic transfer of her text Blue Marrow, we see a cultural revision of “peripheral” creators—the indigenous subject, the woman, the translator—who are now relegated to a secondary rank by the hegemonic literary canon. A translation based on postcolonial and feminist theories, however, allows new audiences to witness Halfe’s subversive spirit, as such a text provides Hispanic American cultures with new experiences and strategies that disturb the dominant language. Halfe’s literature also contributes to a deepening awareness about the role of women in the colonial context and the transmission of memory. La traducción al español de la obra de Louise Halfe es apenas un punto de partida en la reflexión sobre la insuficiente circulación de literaturas autóctonas femeninas en las Américas. Con el traspaso lingüístico de un texto como Blue Marrow, se suscita una triple revalorización cultural de creadores "periféricos" a los que aún el canon literario hegemónico no sitúa en su justo lugar: el sujeto indígena, la mujer, la traductora. Una traducción basada en teorías poscoloniales y feministas extiende la vocación subversiva de Halfe para enriquecer las culturas hispanoamericanas con el aporte de nuevos referentes y estrategias disruptivas de la lengua dominante, así como de una profunda conciencia sobre la mujer en los procesos coloniales y en la transmisión de la memoria.